2013
DOI: 10.1590/s1677-5538.ibju.2013.01.08
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for penile lesions/anomalies in a cohort of Brazilian men ≥ 40 years of age

Abstract: Purpose: To report the prevalence and risk factors of penile lesions/anomalies in a Metropolitan Brazilian city. Materials and Methods: All participants undergoing prostate cancer screening in the city of Curitiba were systematically examined to identify penile lesions including cutaneous mycosis, sexually transmitted diseases, penile cancer, meatal stenosis, hypospadias, and Peyronie's disease. Outcomes of interest included the prevalence and the relative risk and 95% confidence intervals of the lesions/anoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…58 Phimosis was 6.7 times more common in men with a history of diabetes. 39 Phimosis may be a warning sign of diabetes, since 12% of the men with phimosis and who had no previous history of a disorder of glucose metabolism or diabetes were found to have diabetes (8%) or impaired fasting glycemia (4%), that is, diabetes prevalence was higher than the UK average for diabetes of 3.6% at the time of the study. 59 Balanitis is common in diabetes and recurrent infection and scarring is probably responsible for the phimosis that develops.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…58 Phimosis was 6.7 times more common in men with a history of diabetes. 39 Phimosis may be a warning sign of diabetes, since 12% of the men with phimosis and who had no previous history of a disorder of glucose metabolism or diabetes were found to have diabetes (8%) or impaired fasting glycemia (4%), that is, diabetes prevalence was higher than the UK average for diabetes of 3.6% at the time of the study. 59 Balanitis is common in diabetes and recurrent infection and scarring is probably responsible for the phimosis that develops.…”
Section: Discussionmentioning
confidence: 98%
“…[2][3][4] These were sourced as follows. The PubMed search yielded 1455 "hits," of which 27 2,4,14,17,18,20,21,[23][24][25][27][28][29][30][33][34][35][37][38][39][41][42][43]45,46,48,49 fulfilled the inclusion criteria. Google Scholar yielded 4 further articles.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…[50] A Brazilian study of men presenting for prostate cancer screening identified balanoposthitis in 12%. [51] The prevalence was 58% higher in those with a history of nonspecific urethritis. [51] Balanoposthitis is especially common in uncircumcised diabetic men,[205152] a dysfunctional, shrunken penis likely a contributing factor.…”
Section: Resultsmentioning
confidence: 99%
“…[51] The prevalence was 58% higher in those with a history of nonspecific urethritis. [51] Balanoposthitis is especially common in uncircumcised diabetic men,[205152] a dysfunctional, shrunken penis likely a contributing factor. [20] Not surprisingly, balanoposthitis in diabetic men adds to their frequent diabetic neuropathy and peripheral vascular disease, so contributing to their sexual dysfunction.…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence in adult males appears to be low, but it is difficult to determine with accuracy due to differences in demographics and reporting criteria. Primary studies have reported rates of 0.5% among men over age 40 in Brazil (Romero, Romero, Almeida, Oliveira, & Filho, 2013) and 5% among men over age 18 in Rwanda (Bitega et al, 2011). A comprehensive review suggests that the prevalence in adult males is approximately 2% (Shahid, 2012).…”
Section: Circumcision In Men With Phimosismentioning
confidence: 99%